Importance of epicardial adipose tissue as a predictor of heart failure with preserved ejection fraction - Ateş,Kenan (2022)
SUMMARY OBJECTIVE: Epicardial adipose tissue is a special form of visceral fat surrounding the heart. It is associated with cardiac and metabolic diseases. Epicardial adipose tissue is associated with risk factors for heart failure with preserved ejection fraction, such as obesity, metabolic syndrome, hypertension, and diabetes. In this study, we examined the importance of Epicardial adipose tissue as a predictor of heart failure with preserved ejection fraction. METHODS: Patients who were admitted to the Dicle University Medicine Faculty Heart Hospital between November 2013 and August 2014 were recruited for the study. The heart failure group consisted of 30 patients who were admitted to the cardiac intensive care unit, and the control group consisted of 30 patients who were admitted to cardiology polyclinics. We care about patients’ demographic and clinical features to be similar. Heart failure was diagnosed according to the European Cardiology Society 2012 heart failure guidelines. Epicardial adipose tissue was measured with a transthoracic parasternal long axis with an echocardiography device (GE Vivid S6). We compared the Epicardial adipose tissue measurements between the two groups. RESULTS: Epicardial adipose tissue was higher in patients with heart failure with preserved ejection fraction than in the control group (9.21±0.82 and 7.13±1.39 mm, respectively; p<0.001). Echocardiographic findings associated with left ventricular hypertrophy were intact ventricular septum (13.03±0.57 and 12.11±2.22 mm, respectively; p=0.013) and left ventricular mass index (131.13±18.00 and 117.90±20.30 g/m2, respectively; p=0.010). Findings associated with left ventricular diastolic dysfunction were as follows: left atrial volume index (60.71±21.53 and 44.92±9.93 mL/m2, respectively; p<0.001) and E/è (13.87±3.88 and 10.12±2.44, respectively; p<0.001) were higher in patients with heart failure with preserved ejection fraction than in the control group. Body mass index was not a significant indicator of obesity (p=0.097), but waist circumference was a significant indicator of visceral obesity (p<0.001). Logistic regression analyses indicated that Epicardial adipose tissue, age, left atrial volume index, left ventricular mass index, waist circumference, and E/é were significant in the Heart failure group; Epicardial adipose tissue was significant (p=0.012), and waist circumference significance was borderline (p=0.045). CONCLUSIONS: Epicardial adipose tissue was higher in patients with HF than in the control group, and Epicardial adipose tissue was a predictor of heart failure with preserved ejection fraction. In patients with heart failure with preserved ejection fraction, increased Epicardial adipose tissue means that Epicardial adipose tissue can be used as a biomarker of inflammation in the pathophysiology of heart failure with preserved ejection fraction.